Pugalendi prahasana. - GOLDANI (Karlo). 9 (Bengaluru Abhinava Prakashana, 2005)
The Servant of Two Masters (1746) is a famous comedic play written by the Italian playwright Carlo Goldoni
Keywords: Ramanatha